Genetic architecture of Marwari sheep: Growth rate - PANNU, U; BARHAT, N K; SINGH, V K; PANT, K P (The Indian Journal of Animal Sciences, 2013)
Records of 1016 Marwari lambs born from 1987 to 1992 at Central Sheep and Wool Research Institute. Arid Zone Campus, Bikaner. were used to study the effect of selection line, year of birth, sex of lamb and generation on growth. Significant etfect of year of birth was found for absolute growth rate and relative growth rate, while sex of lamb. selection line and generation had signiticant etfect during some periods of absolute growth rate and relative growth rate. Estimates of heritability were low to medium.